Tourism and farmers' economic transformation: lessons from North Toraja - Yusriadi, Yusriadi; Cahaya, Andi; Masriadi, Masriadi (Frontiers in Sustainable Food Systems, 2024)
Farm diversification is becoming increasingly important for farmers in developing countries to improve economic resilience, especially with the increasing instability of agricultural markets. Agritourism, as one of the diversification strategies, can provide farmers with an alternative source of income. However, the factors influencing this diversification decision, particularly in rural areas such as North Toraja, Indonesia, still need to be fully understood. This qualitative research aims to understand the factors that influence farmers' livelihood diversification decisions in North Toraja, focusing on the role of agritourism and its implications for economic resilience and sustainable development. Data was collected through semi-structured interviews with 30 North Toraja farmers who have yet to diversify their businesses. The results showed that farmers' diversification decisions are influenced by several factors, including internal motivation (such as income generation opportunities and lifestyle needs), resource availability (land, capital, skills), market conditions (demand for agricultural products and agritourism services), and accessibility (strategic location and good access). The analysis also revealed that 83% of farmers were motivated by income generation opportunities, while 60% considered capital and location important factors in diversification. Farm diversification through agritourism provides additional income opportunities and contributes to farmers' economic resilience. This research emphasizes that diversification decisions are complex processes influenced by economic, social, and cultural factors. The results of this study provide insights into the dynamics of farmers' diversification decisions and provide policy implications to support sustainable rural development through agritourism.